Economic preferences, trade and institutions - Nico Steffen (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We make use of a comprehensive trade panel data set that includes intra-national ows to identify the effect of national economic preferences - patience, risk attitude, negative reciprocity and pro-social preferences from the Global Preference Survey (GPS) - on external trade in a gravity approach, while still being able to crucially control for multilateral resistances by the proper fixed effects. We use a series of further identification approaches to compare the results and to disentangle channels for the impact of economic preferences on trade. We find that especially patience and risk aversion tend to foster external trade across the board. Additionally, we formally analyze the interaction effects of preferences and institutions. Our findings suggest that preferences may act as substitutes for bad formal institutions to some extent.
Keywords: F10; F14; D01; D91; Z10; 330; Trade determinants; Non-Tariff Barriers; Economic preferences; Sociocultural variation